2017
DOI: 10.18632/oncotarget.14517
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation reveals how phosphorylation of tyrosine 26 of phosphoglycerate mutase 1 upregulates glycolysis and promotes tumor growth

Abstract: Phosphoglycerate mutase 1 (PGAM1) catalyzes the eighth step of glycolysis and is often found upregulated in cancer cells. To test the hypothesis that the phosphorylation of tyrosine 26 residue of PGAM1 greatly enhances its activity, we performed both conventional and steered molecular dynamics simulations on the binding and unbinding of PGAM1 to its substrates, with tyrosine 26 either phosphorylated or not. We analyzed the simulated data in terms of structural stability, hydrogen bond formation, binding free e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
(51 reference statements)
1
12
0
Order By: Relevance
“…PGAM catalyzes the conversion of 3-phosphoglycerate to 2-phosphoglycerate, which is a crucial step in glycolysis. Previous phosphoproteomics studies showed that PGAM can be phosphorylated at multiple tyrosine sites, which enhances PGAM activity and upregulates glycolysis [41, 42]. In this study, phosphorylated PGAM was down-regulated only in C101LAC 12 h after SA treatment.…”
Section: Discussionsupporting
confidence: 46%
“…PGAM catalyzes the conversion of 3-phosphoglycerate to 2-phosphoglycerate, which is a crucial step in glycolysis. Previous phosphoproteomics studies showed that PGAM can be phosphorylated at multiple tyrosine sites, which enhances PGAM activity and upregulates glycolysis [41, 42]. In this study, phosphorylated PGAM was down-regulated only in C101LAC 12 h after SA treatment.…”
Section: Discussionsupporting
confidence: 46%
“…Thus, simulations are expected to be effective for increasingly more complex systems. Larger number of atoms and longer simulation time frames become accessible to reproduce realistic binding/unbinding events that may occur in biosensor systems [ 120 , 121 , 130 , 131 , 132 , 133 ]. Recently, complete fully atomistic models of capsids such as of HIV-1 and Hepatitis-B viruses were developed [ 134 , 135 , 136 ], which may facilitate much more accurate modeling of interaction events at biosensor/capsid interfaces.…”
Section: Computational Approaches To Lc Sensor Designsmentioning
confidence: 99%
“…The promoting roles of PGAM1 in aggressive tumors have received increasing attention in recent years. Several studies have suggested that PGAM1 promoted tumor growth by upregulating the glycolysis process 9,10 . In a research from Hitosugi et al 11 , the phosphorylation of PGAM1 (Y26) induced by oncogenic tyrosine kinases has been shown to activate its activity and promote tumor growth.…”
Section: Introductionmentioning
confidence: 99%